Paeoniflorin Inhibits ASK1-TF Axis by Up-Regulating SOCS3 to Alleviate Radiation Enteritis - Sheng, Lei; Hu, Fan; Yu, Hanqing; Tao, Xueyou; Jia, Rumeng; Gu, Yufeng; Chen, Lu; Kong, Hong; Miao, Chen; Fei, Wenjing; Yang, Yang; Jia, Jinhui; et al. (Frontiers in Pharmacology, 2022)
Radiation enteritis is one of the main adverse effects of radiotherapy, presenting with a poorly understood etiology and limited options for therapy. Intestinal inflammation and ischemia are the core mechanisms of radiation enteritis. Suppressor of cytokine signaling 3 (SOCS3) is an endogenous “inflammation brake.” We hypothesized that paeoniflorin, a pinane monoterpene bitter glycoside, could increase SOCS3 expression to reduce inflammation and ischemia and improve enteritis in mice. Laser Doppler flowmetry was used to detect changes in intestinal blood flow. RAW264.7 and human umbilical vein endothelial cells were used to investigate the mechanism of action of paeoniflorin. It was observed that radiation caused high mortality, intestinal inflammatory responses, and low blood flow in mice. Paeoniflorin effectively alleviated intestinal atrophy, prevented thrombosis, improved radiation enteritis, and reduced mortality in mice undergoing radiotherapy. In addition, paeoniflorin increased the release of growth arrest-specific gene 6 (Gas6) and phosphorylation of the Axl receptor, subsequently inducing the expression of SOCS3 and inhibiting the expression of p-apoptosis signal-regulating kinase 1 and tissue factor in vivo and in vitro. Based on our findings, we suggest that paeoniflorin is potentially effective in alleviating radiation enteritis via the activation of the Gas6/Axl/SOCS3 axis and subsequent reduction in intestinal inflammation and ischemia.